Facile Interface Engineering Enabled Efficient and Stable Self‐Powered Perovskite Photodetectors for Versatile Photosensing Applications - Chang, Chih‐Yu; Chin, Yi‐Ling; Chang, Chun‐Ya; Holovský, Jakub (Advanced functional materials, 2025)
A facile and promising strategy to achieve high‐performance and stable perovskite (PVSK) photodetectors by strategically selecting dibromo‐substituted naphthalene tetracarboxylic diimide (NDI‐Br2) as both electron transport layer (ETL) and ion blocking layer (IBL) is presented. The results signify that strong electron‐withdrawing dibromine substituents endow NDI‐Br2 with proper energy level and high affinity for iodide ions, rendering it well‐suited for acting as ETL and IBL synchronously. With this strategy, the resulting photodetectors exhibit remarkably high responsivity of 0.53 A W−1, specific detectivity of 3.58 × 1014 Jones and linear dynamic range of 217 dB. Very encouragingly, with appropriate encapsulation, superior device stability is secured even under continuous light irradiation or thermal stress conditions. More importantly, the applicability of this strategy to diverse fields, including pulse oximetry, image sensor, and precise ultraviolet (UV)‐A recognition system based on machine learning algorithm, are also validated. This work sets a precedent for developing self‐powered PVSK photodetectors with record‐breaking performance and stability, which represents an important step toward commercialization of this emerging technology. It is confident that this strategy can not only provide new insights in the design of new classes of interfacial layer materials, but also expand the practical applicability of PVSK photodetectors in real‐world scenarios. A promising interface engineering strategy to achieve high‐performance and stable self‐powered perovskite photodetectors is presented by using NDI‐Br2 as electron transport layer and ion blocking layer synchronously. Very encouragingly, the resulting devices achieve record‐breaking performance and stability. Additionally, their wide‐range applications in pulse oximetry, image sensor, and precise UV‐A recognition system based on machine learning algorithm are also demonstrated.